Teaching Speaking Through Song to Improve Students' Speaking Achievement at 7th Grade UPT SMPN 1 Gadingrejo - LILIANA SYAFITRI; Mahpul; Novita Nurdiana (English Language Education Study Program, 2026)
This research was conducted to find out whether the use of English songs can improve students’ speaking achievement in the seventh grade of UPT SMPN 1 Gadingrejo. This study applied a quantitative approach with a pre-experimental design using a one-group pre-test and post-test. The sample consisted of one class of seventh-grade students, and the data were collected through speaking tests assessing pronunciation, fluency, linguistic features, and extra-linguistic features. The results showed that students’ speaking achievement improved after the implementation of English songs, as seen from their better performance in pronunciation, fluency, vocabulary, grammar, and confidence. The statistical analysis also indicated that the significance value was lower than 0.05, meaning that there was a significant difference between the pre-test and post-test scores. In conclusion, the use of English songs is effective in improving students’ speaking achievement and can create a more enjoyable and motivating learning atmosphere. Therefore, English songs can be used as an alternative teaching medium in teaching speaking.